2012
DOI: 10.2319/032612-253.1
|View full text |Cite
|
Sign up to set email alerts
|

Systemic propolis stimulates new bone formation at the expanded suture

Abstract: Objective: To investigate the effects of systemically given propolis on the expanded premaxillary suture in a rat study model. Materials and Methods: The 24 rats were randomly divided into three groups-only expansion (OE), expansion plus propolis (PRO), and nonexpansion (control) groups. After the 5-day expansion period was completed, the OE and PRO groups underwent 12 days of mechanical retention. At the end of this period, the animals were euthanatized and their pre-maxillae were dissected and fixed. Histomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 29 publications
5
49
0
Order By: Relevance
“…During the treatment bone remodeling takes place within the palatine suture. The research carried out by Altan et al on rats confirms positive effect of propolis solution on bone forming process during the treatment with the device to expand the palatine suture [68]. The results of the research show an increased quantity of osteoblasts in preparations from rats which received propolis during the treatment.…”
Section: Use Of Propolis In Dental Specialtiesmentioning
confidence: 83%
“…During the treatment bone remodeling takes place within the palatine suture. The research carried out by Altan et al on rats confirms positive effect of propolis solution on bone forming process during the treatment with the device to expand the palatine suture [68]. The results of the research show an increased quantity of osteoblasts in preparations from rats which received propolis during the treatment.…”
Section: Use Of Propolis In Dental Specialtiesmentioning
confidence: 83%
“…There are many studies investigating the effects of propolis on bone. In a study by Altan et al, effect of systemically applied propolis on the expanded premaxillary suture was studied and it was thought that bone formation in this region could be accelerated [18]. In a study by Guney et al, effects of propolis on fracture healing were examined and the time-dependent, beneficial effects of propolis were discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the antioxidant property of propolis in tissues. In a histomorphometric study, Altan et al [13] showed that propolis stimulated new bone formation in bone suture separation and increased inflammatory cell numbers and capillary numbers in tissues. Guney et al [8] observed a positive effect of propolis on fracture healing; they reported that while radiological scores in the 3rd and 6th weeks were better compared to the control group, histological scores were comparable to those of the control group at the 6th week.…”
Section: Discussionmentioning
confidence: 99%